(untitled) (Bangladesh Journal of Anatomy, 2019)
Context: Stature or height in upright position has an important role in medico-legal practice. In many tragic events or in crime scenes, direct identification of the victims is difficult because only mutilated, decomposed and amputed body fragments may be found. In such situations estimation of stature helps in establishing the biological profile of the victims through examination of the dismembered body parts remain.This study was aimed to investigate the correlation between stature and foot lengths, to derive regression equations for stature estimation from foot lengths and to make comparison with previous studies on other populations. Materials & Methods: This cross-sectional study was carried out at the Anatomy Department of Sir Salimullah Medical College, Dhaka, Bangladesh from January 2017 to December 2017 on 50 male medical and dental students aged between 21 and 26 years. Full foot length (FFL) and truncated foot length (TFL) were measured by MB ruler software. Relationships between stature and foot lengths were obtained by Pearson’s correlation coefficient test. Results: Both FFL and TFL showed significant positive correlation with stature (r = 0.709 and 0.618 respectively). The linear regression equation for stature estimation derived from FFL and TFL were 60.954 + 4.571FFL and 81.687 + 4.915TFL respectively. The linear regression equations derived from FFL have larger correlation coefficient (R), coefficient of determination (R2), adjusted coefficient of determination (adj R2) and smaller standard error of estimation (SEE) than those derived from TFL. Bangladesh Journal of Anatomy January 2019, Vol. 17, No. 1, pp. 5-9